Challenges encountered by Students With Visual Impairment in Accessing Orientation and Mobility Training - Aftab, Muhammad Javed; Bano, Sidra; Iram, Umaila (Annals of Human and Social Sciences, 2024)
This study focused on comparing challenges in orientation and mobility encountered by students with visual impairment in accessing training on the basis of gender, age, Onset of disability, educational level and type of visual impairment. Orientation and mobility training helps visually impaired individuals to explore their environment easily. But encountered challenges in comprehensive orientation and mobility training reduce independence and social inclusion of visually impaired students.By understanding the challenges faced by visually impaired students new and better policies can be develop and more better training sessions regarding trainings can be arrange for visually impaired students.Data was collected from 104 students with visual impairment from lahore, Pakistan through questionnaire approach. And the self developed questionnaire consists of 20 items. Statistical analysis was conducted through Statistical Package for Social Sciences (SPSS) including t test and ANOVA and the results showed significant differences in orientation and mobility challenges faced by visually impaired students on the biases of gender, age, Onset of disability, Educational level and type of visual impairment. Findings of this study emphasize on the importance of orientation and mobility training programs to identify special needs of visually impaired students and maximize social inclusion and independence. Recommendations include providing qualified orientation and mobility professionals, training and independence to visually impaired students.